On the importance of altruism, prosocial behavior and Christian love in behavioral economics research - Rati Mekvabishvili (Economic Thought, 2023)
The article discusses the concepts of altruism and prosocial behavior and their importance in interdisciplinary studies of behavioral economics. The basic theoretical models and concepts of altruism in Behavioral Economics are reviewed. Altruism is shown to be a hidden and complicated form of selfishness. In essence, altruism and prosociality are therefore not fundamentally different concepts: both are ultimately self-oriented. In the article, we take the Christian worldview and compare altruism with Christian love and discuss their differences and the importance of their theoretical and practical implications. We show that altruism and Christian love are not only diverse but contradictory concepts, which in our opinion is of great importance at least in terms of promoting a well-being of human society.
Keywords: 330; Altruism; Prosocial Behavior; Christian Love; Christian Worldview; Evolutionary Worldview; Behavioral Economics